KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL BANGUN DATAR GABUNGAN - Zahra Agnia Dewi; Dori Lukman Hakim (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Geometry is a branch of mathematics taught at all levels of education. One of the foundations in understanding geometry is flat shapes, especially combined flat shapes. However, students' ability to solve combined flat-shape problems requires special attention. This research will look at students' abilities in solving combined flat shape problems, to describe students' abilities in applying the concepts of area and perimeter of combined flat shapes. Qualitative descriptive methods will be used to examine this research. The research will be carried out at one of the Junior High Schools (SMP) in Karawang Regency, with research subjects consisting of 15 class IX students. Data will be collected through a written test taken from the 2013 Curriculum Package Book (Mathematics) 2017 Revised Edition with 3 questions. From the results of this research, it was concluded that students' ability to solve combined flat-shape problems was considered quite good. This can be seen from the written test where the majority of students have understood the concept of combined plane shapes by following the appropriate processing steps and showing expertise in mathematical calculations. However, most students are still unable to identify information at the beginning of the problem. Therefore, a little effort is needed to develop students' abilities in solving problems, especially in identifying information.